The Pretzel knot: a new simple locking slip-knot - (:unkn) unknown (SPRINGER, 2010)
Arthroscopic knot tying is an important part of arthroscopic shoulder surgery. The Pretzel knot is a new locking slip-knot, which is simple to learn and prepare. It can slide easily to maintain desired tension and can be locked by a simple maneuver.
Keywords: Shoulder arthroscopy; Sliding knot; Locking knot; Arthroscopic knot; Slip knot